2009
DOI: 10.1177/0193945909333890
|View full text |Cite
|
Sign up to set email alerts
|

Severe Fatigue and Depressive Symptoms in Lower-Income Urban Postpartum Women

Abstract: The purpose of this study was to identify whether severe postpartum fatigue at 1 and 3 months postpartum was associated with depressive symptomatology at 6 months in lower-income urban women. A convenience sample of 43 lower-income postpartum women completed the Modified Fatigue Symptoms Checklist and Edinburgh Postpartum Depression scale at 1, 3, and 6 months postpartum. Participants who were severely fatigued at both 1 and 3 months postpartum were significantly more likely to exhibit depressive symptomatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 37 publications
4
31
0
1
Order By: Relevance
“…Severely and chronically sleep deprived mothers may be less able to meet the socioemotional needs of their infants and children and the daily demands of their lives, which in turn, may affect the household’s overall economic health. Our findings are comparable with a prior study that found that 44% of the sample met the criteria of “severe fatigue” at both 1 and 3 months postpartum (Doering Runquist, Morin, & Stetzer, 2009). Nurses can tailor interventions to meet the needs of women with severe and persistent postpartum fatigue and poor sleep.…”
Section: Clinical Nursing Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…Severely and chronically sleep deprived mothers may be less able to meet the socioemotional needs of their infants and children and the daily demands of their lives, which in turn, may affect the household’s overall economic health. Our findings are comparable with a prior study that found that 44% of the sample met the criteria of “severe fatigue” at both 1 and 3 months postpartum (Doering Runquist, Morin, & Stetzer, 2009). Nurses can tailor interventions to meet the needs of women with severe and persistent postpartum fatigue and poor sleep.…”
Section: Clinical Nursing Implicationssupporting
confidence: 90%
“…Excluding women with a past or current sleep or depression diagnosis was a limitation of our study and likely a reason for the low levels of depressive symptoms noted, especially given that studies in similar populations note that 25 to 40% percent of women score in a referable range (Doering Runquist et al, 2009). It is possible that a more representative sample that includes past or current depression may have resulted in even poorer sleep than that reported here.…”
Section: Clinical Nursing Implicationsmentioning
confidence: 99%
“…Evdeki sorumluluk kadının üzerinden alınmalı ya da sorumlulukları azaltılmalıdır (20,21) . Doğum sonrası yorgunluk ile ilgili literatür incelendiğinde, araştırmaların beslenme (22) , uyku (10,23) , bebeğin beslenme şekli (24) , depresyon (12,(25)(26)(27) , bebek bakım aktivitelerinde güçlük yaşama ve anne-bebek etkileşimi (8) , kaslarda laktik asit birikimi, demir eksikliği anemisi, enfeksiyon, troid disfonksiyonu, nöroendokrin ve immün sistem hastalıkları (28) gibi konulara odaklandığı görülmektedir. Ancak, doğum sonrası yorgunluk ve özbakım gücü arasındaki ilişki-nin incelendiği herhangi bir araştırmaya rastlanmamış ve bu konunun araştırılması planlanmıştır.…”
Section: Introductionunclassified
“…At low levels, fatigue and sleep deprivation are perhaps adaptive by naturally keeping mothers near home while healing from childbirth. On the other hand, severe fatigue and sleep difficulties after childbirth are maladaptive by contributing to adverse health outcomes including reduced breastfeeding duration and functional status, subclinical and clinical depression, and the host of short-and long-term effects of untreated depression on infants and families (Brand & Brennan, 2009; Dorheim, Bondevik, Eberhard-Gran, & Bjorvatn, 2009; Parks, Lenz, Milligan, & Han, 1999; Pugh & Milligan, 1998; Runquist-Doering, Morin, & Stetzer, 2009; Rychnovsky, 2007). …”
mentioning
confidence: 99%